Pelatihan Pembuatan Roll Cake Batik Pada PKK Kelurahan Mojo Kecamatan Gubeng Surabaya - Rina Asmaul; Susilowati; Diana Evawati (LPPM Universitas Yudharta Pasuruan, 2021)
Industrial growth in the food sector in Indonesia is quite good, especially in Surabaya. The training in cake making encourages the emergence of various kinds of cakes that are used as souvenirs for typical Surabaya cakes. The training on making batik roll cakes is expected to bring up creative ideas in cake making. The training method here uses lecture and demonstration methods, the target is PKK women where the implementation is in Urban village Mojo district Gubeng Surabaya. The result of the training on making batik roll cakes is that PKK women are very enthusiastic in making batik roll cakes. The results of making roll cakes can be developed as a business, especially as a cake icon located in Urban village Mojo district Gubeng Surabaya, so that the family's economy can increase.